'Abundantly replenisht with Books of his own purchasing and choyce': Lord Herbert of Cherbury's Library at Montgomery Castle. (May 2015) - Roberts, Dunstan
Abstract : This article considers the library which Edward, first Lord Herbert of Cherbury (1582?–1648), established at Montgomery Castle, in the Welsh Marches. The library was built as part of a major renovation of the castle in 1622–25, during which part of the medieval fabric was replaced with a fashionable brick mansion. The castle was among the casualties of the Civil War, being surrendered to Parliamentarian forces in 1644 and was demolished in 1649. The article discusses the likely movements of the library's contents following the castle's destruction and especially how part of it reached Powis Castle, near Welshpool, in the eighteenth or nineteenth century. It then combines information about books still housed at Powis Castle with information gained from sale catalogues to establish the identities of around 250 of the books which were present at Montgomery Castle. It concludes with a summary description of the books, making particular reference to works of vernacular poetry and romance which may have influenced Lord Herbert in the composition of his famous autobiography.